Quality of Life of Diabetic Foot Ulcer Patients with Hyperbaric Oxygen Therapy - Kusnanto, Kusnanto; Dismalyansa, Dismalyansa; Pradanie, Retnayu; Arifin, Hidayat (Folia Medica Indonesiana, 2019)
DM with ulcer can result in a decrease in the quality of life of patients and need to reduce the intensity of pain and odor on the ulcer, preventing amputation and Hyperbaric Oxygen as an adjuvant therapy in accelerating wound healing. This study aims to explain the effect of HBO on the quality of life of patients with diabetic foot ulcers at RSAL Dr. Ramelan Surabaya. Methods: The research used quasi-experimental design with a non-equivalent control group design approach. The samples were 70 patients from population of all diabetes patients who suffered from diabetic foot ulcers at RSAL Dr. Ramelan. Data were collected by WHOQOL-BREF questionnaire. Analyzed byWilcoxon signed rank test and Mann Whitney U test. Result: Mann Whitney in the post test, the physical p-value domain (0.000), psychological domain (0.012), social domain (0.003), and environmental domain (0,001), where the intervention group has a better value than the control group. Wilcoxon signed rank test results on the physical domain (0,000), psychological (0,012), social (0,003), and environmental (0,001), meaning there were significant differences between pre post test in intervention group. Discussion: Diabetes mellitus patients with foot ulcers given hyperbaric oxygen showed improvement on wound condition, thus reducing pain and medical needs. This makes patients motivated, reduce anxiety, and improve interpersonal support and confidence. Therefore, it is necessary to socialize the effect of HBO on DM patients with foot ulcer, as a treatment option in improving the quality of life of DM patients with foot ulcers.